Power Flow Analysis and Transmission Efficiency Calculation of RV-like Reducers - Xu Yongshuai; Lei Yan; Zhang Shaolong (Jixie chuandong)
A kind of RV-like reducer is proposed. Taking the reducer as a model and according to its structural principle, the single-loop XP system type is derived. Based on the single-loop XP system, the reducer speed, the torque and the power matrix are established and the reducer input and output power matrix is obtained; the power flow direction of each component is analyzed, the power flow direction is mapped to the single-loop XP system, and the reducer power flow model is established; a conclusion has been drawn that the RV reducer has no internal circulation power and the overall transmission efficiency of the reducer is relatively high. The transmission efficiency of the reducer is calculated as an example and the overall transmission efficiency can theoretically reach 0.821 0.